The effects of entrepreneurial marketing and relationship marketing strategies on the performance of small and medium enterprises in Bangladesh - Hoque, Abu Shams Mohammad Mahmudul
Small and Medium Enterprises (SMEs) are one of the essential approaches to economic freedom around the world. However, SMEs can only uphold such a position when proper marketing trategies and appropriate entrepreneurial behavior are exercised in the right place and at the right time to gain positive effects on performance. Despite the position of SMEs to the national economy in Bangladesh, it seems that numerous SMEs failed to operate at the very early stage of setup or within a few years of starting their operational activity due to lack of proper marketing strategy, inappropriate entrepreneurial behavior, weak capital structure, as well as poor relationship with customers. Consequently, the SME sector is under incredible strain, and it has failed to provide maximum advantages and to minimize economic problems of Bangladesh. Even though the significant effects of entrepreneurial marketing and relationship marketing strategies on SMEs performance in developed countries have been observed, the necessity of these strategy orientations is still overlooked by the researchers in the underdeveloped and emerging countries, especially in Bangladesh. Thus, the aim of this study is to investigate the effects of entrepreneurial marketing and relationship marketing strategies' orientation on the performance of Bangladeshi SMEs, taking into consideration of organizational culture and social media. This study used a quantitative method, and a cross-sectional study was carried out through elf-administered questionnaires. The target population of this study was the owners of SMEs' in Bangladesh. Cluster random ampling was used to select 386 owners of SMEs as respondents. Data were analyzed using Structural Equation Modeling (SEM) through the Statistical Package for Social Sciences-Analysis of Moments Structures (SPSS AMOS) software version 25.0. This study found that entrepreneurial marketing strategy, as well as the relationship marketing strategy, had significant direct and indirect effects on the performance of SMEs in Bangladesh. It was also found that the organizational culture of SMEs had a significant effect on the performance of SMEs in Bangladesh. The mediation tests demonstrated that the organizational culture acted as a partial mediator role in the relationship between entrepreneurial marketing strategy and the performance of SMEs, as well as in the relationship between relationship marketing strategy and performance of SMEs in Bangladesh, since both the direct relationships are still statistically significant by the data of the study. Furthermore, this study found that social media moderated the relationship between organizational culture and the performance of MEs in Bangladesh. It can be concluded that entrepreneurial marketing and relationship marketing strategies and organizational culture may affect SME performance in the context of underdeveloped countries. The empirical findings of the present study provide the basis for recommendations for SMEs in enhancing their performance, and for policy-makers to design entrepreneurial support programs and initiatives for SMEs.